A comparative study of malocclusion and its severity in the Ottoman period and modern populations. (18th April 2022) - Shalish, Miriam; Hager, Roee; Brin, Ilana; Ben‐Bassat, Yocheved; Khalifa, Ahmed; Zini, Avraham; Faerman, Marina
Abstract: Malocclusion is a well‐known phenomenon since antiquity. Previous studies found an increase in malocclusion in the modern population. This study was undertaken to assess the frequency and severity of malocclusions in a sample of ancient skulls and to compare these findings with a modern sample, using the same examination protocol. The archaeological sample comprised 63 skulls from Dor, northern Israel, dated to the 16th–19th centuries. Skull examination was performed in maximal occlusion by using a clinically based approach. The modern sample comprised a random, ethnicity‐matched group of 340 school students, aged 11–16 years, who underwent a clinical orthodontic examination. The following parameters were recorded for both groups: Angle's classification, overjet, overbite, crowding, spacing, midlines, and crossbite. Descriptive statistics was obtained for all the parameters examined, and the results were compared between the groups. Differences were considered significant at p < 0.05. The frequency of the occlusal relationships according to Angle's classification in the two groups was different, although the difference did not reach statistical significance ( p = 0.471). However, the main difference between the two groups was recorded in Angle's Class I malocclusion, which was remarkably more prevalent in the modern population, and in a higher prevalence of normal occlusion in the archaeological group. The distribution of malocclusion severity was significantly different in the two groups ( p < 0.01). Frequency of crowding in the maxilla (33.9% vs. 15.4%) and mandible (55.3% vs. 29.6%) was significantly higher in the modern group ( p < 0.01). The frequency of open bite was higher in the archaeological group ( p < 0.01). The secular trend observed in this study could be attributed to poor oral health and inadequate food supply in the past, as well as changes in food processing over the years.